Sistema informático de inventario y facturación de mercadería con entorno web en la imprenta y gráficas Chone - Lucas Chávez, Geomara Juliana (2013)
The primary objective of this research was to create a web information system in order to improve inventory control and billing of merchandise in the Printing and Graphic Chone, with the firm intention to streamline processes and to facilitate the work of this institution. The software model was used for the preparation of the application was the model UWE (UML-based Web Engineering / Engineering Web based UML), which allowed the collection of information to define requirements and system architecture. Were developed use cases and data flow diagrams that helped describe what the system should do. Then he proceeded to develop the database in MySQL Workbench which was coupled to the treatment and handling of information. Following this GUI was developed with the help system from a storyboard and a CSS template then joined the application logic by programming in three layers, the effect was used for the development platform Dreamweaver CS5. Purchased SSL security certificate to protect your software application and help improve the confidence of the website, once validated system function was verified use with satisfaction.